Workplace motivation among the technicians of Raisevest Sdn Bhd / Noor Asikin Ab Rahman - Ab Rahman, Noor Asikin (Faculty of Business and Management, 2009)
Motivation is very important in an organization. With more competitive working environment, high performance organizations have emphasized their focus on human resource as the most important resource for the organization. Self-directed teams and total quality management are also emphasized as important in the process of sustaining growth within organizations. It is very important that the company recognizes the basic needs of the employees as well as their higher level of needs in order to achieve job satisfaction and motivation that would employees contribute to the targets and goals of the organization. Raisevest Sdn Bhd sees itself as the top distributors for parking industry in global business. Raisevest Sdn Bhd would be able to increase their profit and services through higher level of job motivation of employees that would help the company thrive in a more competitive environment. Through meeting needs of administration, they would be able to maintain and sustain growth of the company. The profit and high level services would be achieved through their ability to motivate their employees to attain the goals of organization. In this study, researcher found that employer faced problem towards employee dissatisfaction of reward received from the company. Dissatisfaction problem among employee towards reward received will lead to the motivation level and job performance of the employee. In addition, employee also dissatisfied with the company practices. Employer doesn’t have a chance to give opinion and top management difficult to spend time seat together with employee and discuss the problem. In this study, researcher will find the best strategy to motivate employees in order to increase their job performance. They need the best strategy to boost up employee’s motivation and at the same time leads to the high job performance. This study is based on the primary and secondary data through observation and discussion with the top management as we as. The findings from the study will be used to offer recommendations that would be highlighted to the company management.